Sistem Preventive Maintenance Berbasis Web dengan Menggunakan Algoritma Priority Scheduling pada PT. Beta Pharmacon - Bayu Priyatna; Topan Trianto; Julifer P Manurung; Nono Heryana; Arip Solehudin (Masoem University, 2020)
PT. Beta Pharmacon in the actual preparation of Preventive Maintenance (PM) schedules and input of reports or preventive results data still uses Microsoft Excel, and preventive schedules that have been made are sometimes not following the actual because the machine cannot be maintained (the production process has not been completed) so that the schedule has been completed. Determined to change and to confirm whether preventive maintenance can be done every day, still by telephone. Based on the above problems, a web-based Preventive Maintenance System will be created using the priority scheduling algorithm. The web is built using the CodeIgniter framework and database using MySQL. With this system, it can facilitate scheduling of preventive maintenance, data collection of machines and tools in the company, search for data on preventive maintenance results, coordination of the implementation of preventive maintenance, so that it can provide the information needed effectively and efficiently.